Current state of treatment for lower extremity acute deep venous thrombosis (a literature review) - A. O. Nykonenko; Y. M. Vailo; A. M. Materukhin (Zaporožskij Medicinskij Žurnal)
Despite the use of modern methods of diagnosis and treatment, deep vein thrombosis (DVT) of the lower extremities remains a fairly common disease. In half of all cases, DVT may be asymptomatic and manifest itself in subsequent symptoms of pulmonary embolism (PE) or postthrombotic syndrome (PTS). An important role in the pathogenesis of this disease is played by a variety of factors and conditions that contribute to thrombosis in the venous vessels of the lower extremities, as well as impaired venous outflow from the lower extremity due to blockage of the venous lumen by such a thrombus. The action of various treatments is aimed at certain links in the pathogenesis, namely: anticoagulant therapy prevents further thrombosis, thrombolysis dissolves blood clots, surgical and mechanical thrombectomy remove blood clots from the lumen of the vein, lysis or removal of thrombotic masses restores thrombosis in the small circle of blood circulation. There is no single, universal method for combating DVT. In addition, there are new methods, such as the use of devices for pharmaco-mechanical thrombolysis, stent-retrievers which need to be tested for effectiveness and safety, as well as for a comparative analysis with existing treatments.